Development and Validation of the Pediatric Charcot–Marie–Tooth Disease Quality of Life Outcome Measure. Issue 2 (7th December 2020) - Ramchandren, Sindhu; Wu, Tong Tong; Finkel, Richard S.; Siskind, Carly E.; Feely, Shawna M. E.; Burns, Joshua; Reilly, Mary M.; Estilow, Timothy; Shy, Michael E.; ,
Abstract : Objective: Charcot–Marie–Tooth disease (CMT) reduces health‐related quality of life (QOL), especially in children. Defining QOL in pediatric CMT can help physicians monitor disease burden clinically and in trials. We identified items pertaining to QOL in children with CMT and conducted validation studies to develop a pediatric CMT‐specific QOL outcome measure (pCMT‐QOL). Methods: Development and validation of the pCMT‐QOL patient‐reported outcome measure were iterative, involving identifying relevant domains, item pool generation, prospective pilot testing and clinical assessments, structured focus‐group interviews, and psychometric testing. Testing was conducted in children with CMT seen at participating sites from the USA, United Kingdom, and Australia. Results: We conducted systematic literature reviews and analysis of generic QOL measures to identify 6 domains relevant to QOL in children with CMT. Sixty items corresponding to those domains were developed de novo, or identified from literature review and CMT‐specific modification of items from the pediatric Neuro‐QOL measures. The draft version underwent prospective feasibility and face content validity assessments to develop a working version of the pCMT‐QOL measure. From 2010 to 2016, the pCMT‐QOL working version was administered to 398 children aged 8 to 18 years seen at the participating study sites of the Inherited Neuropathies Consortium. The resulting data underwent rigorous psychometric analysis, including factor analysis, test–retest reliability, internal consistency, convergent validity, item response theory analysis, and longitudinal analysis, to develop the final pCMT‐QOL patient‐reported outcome measure. Interpretation: The pCMT‐QOL patient‐reported outcome measure is a reliable, valid, and sensitive measure of health‐related QOL for children with CMT. ANN NEUROL 2021;89:369–379